Pop competitiveness - Cellini, Roberto; Soci, Anna (PSL Quarterly Review, 2012)
Very few economic terms are used as much as competitiveness in economics. This article deals with the different meanings of competitiveness, at the level of a firm, at the level of the local area, and at the level of the country. It analyzes the problems of consistency among the available definitions and among the indicators used to measure competitiveness. JEL Codes: F13, F23, F32